A Study Of Angiogenesis In Human Colorectal Tumors By Using Anti-Cd34 Antibody. (Assessment By Light Microscope And Computer–Aided Image Analysis System) - Salmo, Nabil; Hussain, Alaa’ Ghani; Najim, Meethaq Moeen (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Angiogenesis plays a crucial role in tumorigensis; several reports have described a significant increase in microvessel density (MVD) in colorectal carcinogenesis There are several methods to measure the angiogenesis in neoplasms, but immunohitochemistry seems to be the mainstay of all. This method enable us to measure the tumor microvessel densities highlighted by using antibodies directed against endothelial cell markers like CD31,CD34 or others; then assessment of MVD by manual count of the number of microvessels in what appears to be the most vascular area of the tumor(called the hot spot) using a protocol described by Weidner et al.Automated cellular imaging system is used to analyze immunohistochemically stained slides .studies have shown that the device offers accurate precision and reproducibility of immunostained slide analysis exceeding that possible with manual evaluation which was the prevalent method. Aims of the study: To assess the angiogenesis in normal, adenomatous (benign) and malignant colorectal tissues using CD34 and the microvessels will be measured both manually by hot spot method as the MVD and by the use of computerized image analysis system as fraction area ,we correlate between microvessels density and fraction area with various clinicopathological parameters in colorectal cancer (CRC), and to a compare between the results which obtained from both methods. Methods: Paraffin embedded archival materials from 50 cases including three normal resection (non tumoruos) margins, 12 benign colonic lesions and 35 colonic adenocarcinoma were used . 5mm section were cut and they were stained by anti CD34 antibody Angiogenesis was measured as MVD by two methods : manually by light microscope and by a computer image analysis system (as fraction area). Then the MVD and fraction area were correlated with different clinicopathological parameters. Results : This study demonstrate that there is a statistical difference in MVD and fraction area in both hot spot method and CIAS respectively between benign and malignant tumors . P value < 0.05 in hot spot method and less than 0.001 in CIAS and there was highly significant correlation between MVD and fraction area with the grade . There was significant increase in MVD and fraction area from well differentiated to moderately differentiated and to poorly differentiated .There was no significant correlation between MVD and lymph node involvement by hot spot method but CIAS proved a significant correlation between fraction area and lymph node involvement.Both methods (hot spot and CIAS) proved no significant correlation with age , sex , size of the tumor , site of the tumor , stage of the tumor and the number of lymph node involverment.